Osmotic drug delivery system of valsartan (International Journal of Research in Pharmaceutical Sciences and Technology, 2024)
The objective of this study is to design and evaluate a new EOP called swellable elementary osmotic pump (SEOP) of the freely water soluble drug, amitriptyline hydrochloride (1 g /mL) by adding water swellable polymers in the core. The hydrophilic polymers included in the core retard the highly water soluble drug by producing hydrogel within the core, which may restrict and delay the solvent contact with drug molecules and may increase the diffusional length of the solvent to achieve a constant release rate. Thus, this technology can be exploited to achieve constant drug release at predetermined rate especially for highly water soluble drugs.